Serological Evidence of Hepatitis E Virus Infection in an Indigenous North American Population. (2007) - Minuk, GY; Sun, A; Sun, DF; Uhanova, J; Nicolle, LE; Larke, B; Giulivi, A
Abstract : BACKGROUND: Hepatitis E virus (HEV) infections are thought to be uncommon in North America. Recently, HEV transmission has been reported following the consumption of deer meat. Because deer are closely related to caribou and caribou meat is a staple of the Canadian Inuit and the American Eskimo diet, the present study explored the seroprevalence of HEV infection in an isolated Canadian Inuit community. METHODS: Stored sera were thawed and tested for immunoglobulin (Ig) G and IgM anti-HEV by ELISA, and tested for HEV-RNA by reverse transcriptase polymerase chain reaction. RESULTS: The study consisted of 393 sera (representing approximately 50% of the community's inhabitants). Eleven samples (3%) were IgG anti-HEV-positive. Their mean age was 29±8 years and three were male. Two of 11 (18%) were also IgM anti-HEV-positive. All IgG anti-HEV-positive individuals were HEV-RNA-negative. Liver biochemistry was normal in all. Seven of 11 (64%) were also positive for anti-hepatitis A virus, five (46%) were hepatitis B virus seropositive and none (0%) were positive for anti-hepatitis C virus. There were no associations between infections with HEV and other hepatropic viruses. Serological testing was negative for HEV infection in 25 caribou from an adjacent region. CONCLUSION: The results of the present study showed that serological evidence of HEV infection was present in 3% of the observed Canadian Inuit population; the presence of IgM anti-HEV suggested recent infection and HEV did not appear to coinfect with other common hepatotropic viruses. The source of HEV infection in the population remains unclear. These findings are interesting but preliminary. Additional data are required to determine whether HEV infections are responsible for otherwise unexplained acute hepatitis in the Canadian Inuit population and visitors returning from northern North American communities.